Hubungan Pengukuran Nilai Wajar dan Penyajian Kembali Laporan Keuangan: - Rahmat Riandi; Nurzi Sebrina; Vanica Serly (Universitas Negeri Padang, 2019)
This research aims to find empirical evidence regarding the relationship between the measurements of fair value with restatement. The population in this research is the entire financial sector companies were listed on the Indonesia stock exchange (BEI) in 2014-2017. The testing in this research was conducted using binomial logistic regression. The result shows that the fair value measurements does not affect accounting restatement. Size and leverage does not affect a restatement. For further research could consider the sample by comparing the measurement of fair value on financial firms with non-financial companies. For further research could use other variables that might affect a restatement